2002
DOI: 10.1007/s00134-002-1375-6
|View full text |Cite
|
Sign up to set email alerts
|

Short-term cardiovascular effects of plasmapheresis in norepinephrine-refractory septic shock

Abstract: In patients with norepinephrine-refractory septic shock no directional changes in measured variables were found in the first 24 h after a plasmapheresis. Thus, regarding the cost (ca. 1000 euros per separation) and possible risks the procedure needs rigorous evaluation even as "rescue therapy" in patients with septic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…In the present study, plasmapheresis did not improve the hemodynamics. This is in accordance with a recent retrospective study by Ataman et al [18] who failed to demonstrate any significant improvement in cardiovascular parameters during the first 24 h after plasmapheresis.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the present study, plasmapheresis did not improve the hemodynamics. This is in accordance with a recent retrospective study by Ataman et al [18] who failed to demonstrate any significant improvement in cardiovascular parameters during the first 24 h after plasmapheresis.…”
Section: Discussionsupporting
confidence: 81%
“…In the study by Ataman et al [18] the mean duration of sepsis was 5 days and that of septic shock 2 days before plasmapheresis was performed. In the present study we initiated treatment with plasmapheresis within 40 min after the infusion of endotoxin to evaluate if this early intervention could diminish the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…The obvious conclusion is therefore not to hesitate in transiently increasing the dosage of catecholamines if the patient is vasoplegic and hyperkinetic (although this remains experimental) or to use alternative therapies [57]. In this particular case, which is associated with a dramatic prognosis, other agents such as vasopressin or terlipressin [58], methylene blue [59], high volume hemofiltration [60], or plasmapheresis [61] have demonstrated their efficiency in case report studies or small series.…”
Section: Catecholaminesmentioning
confidence: 97%
“…The ability of plasma manipulation to change the levels of circulating mediators appears to depend on the method that is used. Conventional plasma exchange does not consistently affect plasma or serum levels of interleukin-6, interleukin-6 receptor, tumor necrosis factor-α, tumor necrosis factor-α receptor, or C-reactive protein [180][181][182]. By comparison, continuous plasmafiltration or selective adsorption techniques can reduce various inflammatory cytokine levels and may improve hemodynamic parameters in some patients [183][184][185][186][187].…”
Section: Miscellaneous Conditions In Severely Ill Patientsmentioning
confidence: 99%
“…Plasma exchange, either alone or combined with hemofiltration, has been more widely used and evaluated in the critical care setting [reviewed in 117,185,189]. Recent observational studies in patients with sepsis and/or MODS (including many with renal failure requiring peritoneal dialysis, hemodialysis, or hemofiltration) have shown either no effect of exchange or plasmafiltration on cardiovascular parameters [182] and/or mortality [183] or a decrease in early death ranging from 28% (when combined with hemofiltration) [190] to more than 75% [191]. The only published randomized controlled trial demonstrated a 20.5% reduction in the 28-day all-cause mortality (from 53.8% to 33.3%) among patients with severe sepsis or septic shock treated with 1 or 2 daily plasma exchanges (n = 54) compared with untreated control patients (n = 52) [192].…”
Section: Miscellaneous Conditions In Severely Ill Patientsmentioning
confidence: 99%